Peningkatan Menulis Resensi Melalui Model Pembelajaran Kooperatif Tipe STAD Kelas VIII SMP - Jusrin Efendi Pohan (Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to improve the writing ability of eighth-grade students of SMP Negeri 24 Medan City through the implementation of the Student Teams Achievement Division (STAD) cooperative learning model. The method used is Classroom Action Research (CAR) which was implemented in two cycles with 32 students as research subjects. Data collection was carried out through a performance test on writing reviews and student activity observation sheets, while data analysis was carried out qualitatively and quantitatively. The results of the study indicate that the application of the STAD model can improve the writing ability of reviews and student activeness in learning. The improvement in student learning outcomes can be seen from the pre-cycle score of 63.70%, cycle I of 71.29%, and cycle II of 81.11%. Thus, the STAD learning model is effective for use in learning to write reviews.